Hydrosalpinx formation and its regeneration after microsurgical reconstruction: a functional and morphological study on rabbits - Gauwerky, Johannes F. H.; Forssmann, Wolf-Georg; Kurz, M.; Klose, Roger P.; Bastert, Gunther (Human reproduction, 1994)
The development of mechanically induced hydrosalpinx and the subsequent regeneration of the uterine tube following correction were investigated with reference to morphological and functional parameters in 33 rabbits. Mechanically induced hydrosalpinx leads to reduced fertility. The characteristic morphological alterations are flattening of the folds, deciliation, reduced secretory activity and general de-differentiation of the epithelial cells. The intensity of these changes peaked as little as 4 weeks after induction of the hydrosalpinx. The deciliation is generally patchy. The division into different fields, islet formation and celestial chart phenomena reflect different degrees of vascularization and/or oxygenation. These alterations were completely reversible within 8 weeks after reconstruction. In isolated cases only the formation of polypose stumps was seen, which were, however, covered with a normal epithelial surface. The discrepancy between the reduced tubal function following reconstruction for hydrosalpinx and the complete regeneration of the tubal mucosa suggests that other regulatory mechanisms more important for the function of the uterine tube are impaired.